Self-(in)compatibility in Prunus armeniaca L.: Analysis of the S-locus structure and identification of S-haplotype specific S-RNase - Vilanova, S.; Romero, Carlos; Martínez-Calvo, José; Vicente, M.; Llácer, Gerardo; Badenes, María L.; Burgos, Lorenzo (2017)
The gametophytic self-incompatibility (GSI) system in Rosaceae has been proposed to be controlled by two genes located in the S-locus: an S-RNase and a recently-described, pollen-expressed, S-haplotype-specific F-box gene (SFB). Fragments containing genes homologous to the S-RNase and F-box genes in Prunus species have been described. In apricot (Prunus armeniaca L.), these genes were identified recently. Three identified S-RNase alleles and the F-box allelic variants (SFB1, SFB2 and SFB4) allowed elucidation of the S-locus structure in apricot. In this paper, from the analysis of the S-locus, we carried out the molecular typing of several S-alleles in apricot. A primer pair developed from conserved regions identified in the apricot S-locus was used to amplify the first S-RNase intron. Fragments containing the second intron were obtained using two sets of primers designed from published Prunus avium S-cDNA sequences. These results confirm genotypes established by other methods and establish five self-(in)compatibility groups in apricot.